Poland - Allen, Gregory (Lecturer) (London : Kuperard Pub, 2015)
The changes in Polish life, culture, economics, and development have been remarkable. And the pace of change shows little sign of abating. Through twenty-five years of post-Communist transformation and ten years as a member of the European Union, some Polish cities, like Warsaw, Krakow, Pozna, and Wroc aw, have experienced an economic renaissance thanks largely to direct foreign investment, EU funds, and an influx of tourists. Much of the countryside, and cities like od and Lublin, however, are shadows of their former selves. The mass emigration of Polish workers following European integration has had as significant an effect on Poland as it has on the destination countries, such as the UK. Despite a crisis of confidence in the country s direction, a swing toward political populism, and the tragic death of the Polish president in the Smolensk disaster of 2010, Poland is the only EU member not to have suffered economic contraction in the years following the 2007 08 global financial crisis. That Poland continues to develop in growth and influence is a testament to the legendary Polish resolve in the face of adversity. This new, updated edition of Culture Smart! Poland provides visitors with an insight into everyday life in today s Poland. From the country s rich and tragic history to the growth of a modern economy, from the rustic rural countryside to the Warsaw hipster scene, the reader will gain an appreciation of Polish culture much deeper than that to be found in conventional travel guides.
Land and people -- Values and attitudes -- Customs and festivals -- Making friends -- At home -- Time out -- Travel, health, and safety -- Business briefing -- Communicating.
Includes index.
Keywords: Poland -- Social life and customs; Poland -- Description and travel; Etiquette -- Poland; National characteristics, Polish